Field measurements of wind effects on a low-rise building with roof overhang during typhoons. Issue 176 (May 2018) - Wang, X.J.; Li, Q.S.; Yan, B.W.; Li, J.C.
Abstract: Typhoon-induced disasters caused significant economic losses and heavy causalities, most of which resulted from the damage or collapse of low-rise buildings. It is thus necessary to understand the characteristics of typhoon-generated near-surface wind and assess its effects on typical low-rise buildings. In this study, a full-scale low-rise building built in a typhoon-prone region has been instrumented for investigation of the typhoon-induced wind effects on it. This paper presents analysed results measured from the instrumented low-rise building during Typhoons Mujigae and Sarika. The near-surface turbulence intensity, gust factor, turbulence integral length scale and power spectral density were analyzed and discussed. Moreover, the wind-induced pressures on the roof ridge and overhang of the building where were subjected to the most severe suctions under quartering winds are presented and discussed. This field measurement study aims to enhance the understanding of surface-layer wind structures and the wind effects on typical low-rise buildings during typhoons in an effort to reduce windstorm damages to residential buildings. Highlights: A low-rise building was instrumented to monitor wind effects during typhoon landfalls. Turbulence intensities, integral length scales, gust factors, power spectra were analyzed and discussed. Wind pressure characteristics on the roof were investigated. This study provides useful information for design of low-rise buildings in typhoon-prone regions.